A gestão de soluções/sistemas descentralizados em esgotamento sanitário : (des)encontros conceituais e o compartilhamento de responsabilidades entre atores sociais - Washington Lima dos Santos (2022)
The most recent data on the international scenario in sanitation show the significant contribution of this element in the face of the socio-environmental crisis and shed light on the importance of the themes of the 2030 Agenda of the United Nations (UN) and the notes and guidelines of the National Rural Sanitation Program (PNSR), before which the discussion on sustainability and perpetuity of decentralized solutions/systems in sanitation deserves to be highlighted. Assuming commitments in the face of reality consists of considering viable technologies and management models, with a view to providing safely managed services to everyone. Countless people around the world already use decentralized sanitation solutions/systems, and the amount is so expressive that, in 2020, it surpassed the number of people residing in households with connections to the sewage network. That said, despite the current reality of the national sanitation policy, significant advances and controversial updates in legislation, this work aims to: carry out an investigation in the literature on sanitation regarding the management of decentralized solutions/systems, with a view to highlighting occurrences , attributions of existing concepts and experiences. For this, it is based on carrying out searches in the literature aimed at questioning and conceptual discussion crossed with contents and approaches of national policy. Different software were used for data collection, treatment and analysis. The bibliometric analysis made it possible to identify journals, actors, affiliations and international and national research networks in prominence, while the conceptual approaches enabled the grouping and relevant discussions on the subject. In fact, the literature is marked by variations in the use of terms and concepts, regardless of the thematic area. The sector (saneamento, in Brazil) encompasses the sanitation front, whereas, in the international literature, the term 'saneamento' mostly expresses sanitation exclusively. The variations have repercussions on the different uses of terms for framing decentralized solutions/systems in SE and on a practical basis in the mistaken consideration of solutions, for example, by census takers. The international literature highlights that in household surveys, solutions considered as septic tanks are simply 'tanks' (permeable hole without a separate leach field). It is worth highlighting the necessary attention to care that must be taken in comparisons involving sector data; and correct classification on containment of solutions. The specificities related to assisted populations, environments and technologies involved in the management of decentralized sanitaion solutions/systems have required greater understanding of the sharing of responsibilities between social actors, with a view to implementing viable management models – based on instruments of planning, regulation, inspection, provision of services and social control – which need to meet the necessary changes in the face of specific demands. In considering the shared management model, it is worth highlighting the importance of organizing society/community, in such a way as to have legal representation aimed at partnership with the public entity, and distinction from other management models (associative and self-management). When bibliometric analyzes are associated with diverse analyses, important co-authorship networks and contributions present in the literature tend to emerge, whereas, when appropriate, they promote greater literary quality and knowledge networks. The importance of conceptual discussions flow into the horizon of the good applicability of public policies.